Selective Chromogenic Recognition of Copper(II) Ion by Thiacalix[4]arene Tetrasulfonate and Mechanism - Shufang Zhu; Lilin Lu (Molecules, 2020)
Detection of biologically important transition metal ions such as copper by using a simple method is desirable and of great importance. In this work, we firstly reported that water-soluble thiacalix[4]arene tetrasulfonate (TCAS) exhibited selective chromogenic recognition towards copper(II) ion over other transition metal ions. Color change from colorless to salmon pink was observed in TCAS solution, weak bathochromic shift was induced in UV absorption spectrum of TCAS upon addition of copper(II) ion, and the absorbance of characteristic absorption band at 312 nm increased linearly with copper(II) ion concentration. The recognition mechanism of TCAS to copper(II) ion was investigated by a comparative study with calix[4]arene tetrasulfonate (CAS) and time-dependent density functional theory(TD-DFT) study, and the absorption bands were assigned based on transition orbital analysis.